Compaction and mechanical properties of soils compacted in the gyratory compactor - Pérez García, Natalia (2017)
The authors present a series of compaction curves obtained in fine-grained soilsthrough use of a gyratory compactor. The effect on compaction curves of variables such as vertical pressure, angle of gyration, and speed of gyrationis shown. The curves obtained with the gyratory compactor were compared with those obtained using traditional methods of compaction (Proctor standard and modified compaction). It was observedthat the standard compaction curve can be obtained with 200 gyrations, 1.25 degrees of angle of gyration, and a vertical pressure of 200 kPa.On the other hand, with the combination of variables studied in this research, modified compaction curvescould not be reached. Tests were also performed to measure resilient modulus and unconfined compression strength onspecimens prepared at optimum compaction conditions, 2% below the optimum and 2% above the optimum (for Proctor standard tests) using two methodsof compaction.The results indicate that unconfined compressionstrengths and resilient modulus are related to the compaction method when samples are compacted at water content below optimum.